Physical education teachers challenges in implementing school based assessment - Veloo, Arsaythamby; Md Ali, Ruzlan (2016)
School-Based Assessment (SBA) was previously partially implemented in Malaysia.Nevertheless beginning 2011, SBA was made as an educational policy that needs to be implemented in primary as well as lower secondary schools.It presents the understanding, readiness of experienced teachers with regards to the change in the schools assessment approach and how they had implemented SBA in one subject, namely Health and Physical Education (HPE) for lower secondary school.This paper discusses the case of SBA in Physical Education because this subject covers the theoretical as well as the physical implementation aspects.In this qualitative study, 15 secondary day schools in one district in Kedah were randomly selected. A total of 20 Physical Education teachers were then purposively selected from these schools for the interviews.The semi-structured interview sessions was designed to collect information on teacher subject knowledge, availability of assessment facilities and equipment, and Physical Education classroom management to implement SBA.The interview questions were adapted and modified from the Examination Board, Ministry of Education Malaysia (2011).The paper highlights the challenges faced by them and how they overcome those challenges. The finding shows that PEs teachers faced three major challenges namely core knowledge of the subject, assessment facilities and equipment, and classroom management. The impact of SBA on the teachers’ orchestration and design of classroom instructions is also discussed.